METHODS OF CONDUCTING MARKETING RESEARCH IN THE TOURISM SECTOR - Sevinch Eshimova Baxtiyor qizi (Ustozlar uchun, 2025)
Abstract: Marketing research plays a crucial role in the development of the tourism industry by providing valuable insights into consumer preferences, market trends, and competitive positioning. This article explores various methods of conducting marketing research within the tourism sector, highlighting both traditional and modern approaches. The effectiveness of these methods is discussed in the context of identifying tourist needs, enhancing service quality, and fostering sustainable tourism development.